Species of Gnathophausiidae (Crustacea, Lophogastrida) collected off the west coast of Baja California, Mexico, during the TALUD cruises - Hendrickx, Michel E. (Zootaxa, 2019)
During a survey of the deep-water fauna off western Mexico a large series of specimens of Gnathophausiidae was collected in a benthic sledge operating between 296 and 2136 m. Five species known to occur in the area were collected: Gnathophausia scapularis Ortmann, 1906, G. zoea Willemoes-Suhm, 1873, Neognathophausia gigas (Willemoes-Suhm, 1873), N. ingens (Dohrn, 1870), and Fagegnathophausia gracilis (Willemoes-Suhm, 1875). Additional distribution data are provided for these species in the area. A sixth species, G. childressi Casanova, 1996, previously known only from the type locality, off California, was also collected in three localities. Several external morphological characters in F. gracilis are analyzed according to individual size. The general and regional (off western Mexico) distributions of these six species is analyzed.